SPLENIC ARTERY ANEURYSM — FOLLOW UP ON TWO CASES OF ENDOVASCULAR STENT GRAFT TREATMENT - Coelho, A. (2017)
Splenic artery aneurysms are rare, but constitute nearly 60% of all visceral arterial aneurysms. Most patients (80%) are asymptomatic and diagnosed incidentally. Rupture risk is estimated in 3%–10%, with a mortality rate of 25—70%. Elective treatment criteria include symptomatic patients, aneurysms larger than 2 cm in diameter or with rapid enlargement and aneurysms of any size diagnosed in patients with portal hypertension or women of childbearing age; Endovascular treatment is first line of treatment in patients with splenic artery aneurysms, and include several options such as coil embolization, detachable balloon occlusion and stent graft placement. The latter is more suitable for proximally located aneurysms and its main advantage is the potential to preserve splenic blood flow and splenic function. It is noteworthy that stent graft placement to treat splenic artery aneurysms is rarely described in the literature with the largest series having 10 cases, and can be technically challenging due to splenic artery tortuosity. There are no long term results in the literature. In this paper we describe two cases of splenic artery aneurysm repair using stent grafts, with a maximum follow-up of 8 years. We achieved technical success in both cases, with no post-procedure growth, endoleak, kinking, migration re-intervention or other complications. As a conclusion, there is paucity of data on the use of stent grafts in splenic artery aneurysms, however our single center small series results are encouraging with a considerable follow-up period.